Pontocerebellar hypoplasia type 2D and optic nerve atrophy further expand the spectrum associated with selenoprotein biosynthesis deficiency. (May 2016) - Pavlidou, Efterpi; Salpietro, Vincenzo; Phadke, Rahul; Hargreaves, Iain P.; Batten, Leigh; McElreavy, Kenneth; Pitt, Matthew; Mankad, Kshitij; Wilson, Clare; Cutrupi, Maria Concetta; Ruggieri, Martino; McCormick, David; et al.
Abstract: Background: The term Pontocerebellar hypoplasias collectively refers to a group of rare, heterogeneous and progressive disorders, which are frequently inherited in an autosomal recessive manner and usually have a prenatal onset. Mutations in the SEPSECS gene, leading to deficiency in selenoprotein biosynthesis, have been identified in recent times as the molecular etiology of different pre/perinatal onset neurological phenotypes, including cerebello-cerebral atrophy, Pontocerebellar hypoplasia type 2D and progressive encephalopathy with elevated lactate. These disorders share a similar spectrum of central (e.g., brain neurodegeneration with grey and white matter both involved) and peripheral (e.g., spasticity due to axonal neuropathy) nervous system impairment. Case presentation: We hereby describe a 9-year-old boy with (i) a typical Pontocerebellar hypoplasia type 2D phenotype (e.g. profound mental retardation, spastic quadriplegia, ponto-cerebellar hypoplasia and progressive cerebral atrophy); (ii) optic nerve atrophy and (iii) mild secondary mitochondrial myopathy detected by muscle biopsy and respiratory chain enzyme analysis. We performed whole exome sequencing which identified a homozygous mutation of the SEPSECS gene (c.1001T > C), confirming the clinical suspect of Pontocerebellar hypoplasia type 2D. Conclusion: This report further corroborates the notion of a potential secondary mitochondrial dysfunction in the context of selenoprotein biosynthesis deficiency and also adds optic nerve atrophy as a new potential clinical feature within the SEPSECS-associated clinical spectrum. These findings suggest the presence of a possible shared genetic etiology among similar clinical entities characterized by the combination of progressive cerebello-cerebral and optic nerve atrophy and also stress the biological importance of selenoproteins in the regulation of neuronal and metabolic homeostasis. Highlights: Defects in gene SEPSECS are the main cause of pontocerebellar hypoplasia type 2D. Treatment of PCH2D is symptomatic and palliative, while prognosis is guarded. The present case of PCH2D has consisting myopathy with mild mitochondrial abnormalities and optic nerve atrophy, never before been reported. These findings suggest a shared genetic background between PCH2D and optic nerve atrophy. Also it is stressed the biological importance of selenoproteins in the regulation of neuronal and metabolic homeostasis.